Past, present, and future of circRNAs - Patop, Ines Lucia; Wüst, Stas; Kadener, Sebastian (The EMBO journal, 2019)
Exonic circular RNAs (circRNAs) are covalently closed RNA molecules generated by a process named back‐splicing. circRNAs are highly abundant in eukaryotes, and many of them are evolutionary conserved. In metazoans, circular RNAs are expressed in a tissue‐specific manner, are highly stable, and accumulate with age in neural tissues. circRNA biogenesis can regulate the production of the linear RNA counterpart in cis as back‐splicing competes with linear splicing. Recent reports also demonstrate functions for some circRNAs in trans : Certain circRNAs interact with microRNAs, some are translated, and circRNAs have been shown to regulate immune responses and behavior. Here, we review current knowledge about animal circRNAs and summarize new insights into potential circRNA functions, concepts of their origin, and possible future directions in the field. Graphical Abstract This review summarizes the current knowledge on circRNA biogenesis, mechanisms of circRNA expression regulation, their functions and evolution.